Thermal behavior of acidic and alkali activated laterite based geopolymer: a comparative study. Issue 5 (2nd November 2022) - Belinga Essama Boum, Raphael; Mvondo Owono, Francois; Kaze, Cyriaque Rodrigue; Essomba Essomba, Juste Constant; Souleymanou, Bakary; Deutou Nemaleu, Juvenal Giogetti; Ntamak-Nida, Marie Joseph
ABSTRACT: Laterite soils account for 70% of Cameroon territory. The present study aims to investigate the thermal behavior of geopolymer from both thermally activated lateritic clay and indurated laterite at 700°C. The resulting calcined powder was consolidated with phosphoric acid (PA) and alkaline solution (AS), and after 28 days of cure, the geopolymer then was heated at 200°C, 400°C, 600°C, 800°C and 1000°C. At room temperature (25°C), applying an acidic medium developed best mechanical performance (85.6 MPa) using highly indurated laterite (CUPA) than clayey-rich laterite (EMPA) that gave 44.86 MPa. Increasing the heating temperature up to 1000°C greatly affected the samples consolidated with an acid solution than with alkaline medium. This suggests the best stability of N-A-S-H than phosphate binder at high temperature. The high performance of acid-activated samples is related to the alteration of iron minerals in acid medium allowing the formation of Fe-O-P bonds, while the decrease in compressive strength with the increase of heating temperature up to 1000°C is related to the dehydroxylation of formed binder phases that weakened the structure.